PAJERO INOVASI PENGAWET ALAMI UNTUK IKAN DARI LIMBAH JERAMI - Lisniawati Lisniawati; Yaahani Ayu Sholihah; Cristin Hudoyo; Rahmawati Ariyan Chandra; Mieke Dwi Erfani; Arum Suproborini (Universitas Lambung Mangkurat, 2019)
Straw is a by-product of agricultural business in the form of stem stems and leaves of rice plants. Seeds contain cellulose, hemicellulose, Lignin, phenolic, and carbon. Phenolic and carbon content function as preservatives, antioxidants, disinfectants, and biopesticides. The aim of this PKM is to make the latest innovations of natural preservatives that are safe for health. Implementation method used in this program is the planning, product manufacturing, promotion stage, and evaluation phase with. We have marketed